Central bank communication and output stabilization - Sylvester C. W. Eijffinger; Marco Hoeberichts; Mewael F. Tesfaselassie (Centre for Economic Policy Research (CEPR), 2004)
Some central banks have a reputation for being secretive. A justification for this behaviour that we find in the literature is that being transparent about operations and beliefs hinders the central bank in achieving the best outcome. In other words, a central bank needs flexibility and therefore cannot be fully transparent. Using a forward-looking New-Keynesian model, we find exactly the opposite. A central bank that is conservative improves output stabilization by being transparent about the procedures it uses to assess the economy and, especially, about the forecast errors it makes. Under certain conditions transparency by a conservative central bank also improves interest rate stabilization. We also find that higher transparency makes it optimal for the central bank to be more conservative as the benefits from higher transparency in terns of output stabilization are greater the more conservative the central bank is.
Keywords: D83; E52; E58; 330; Zentralbank; Öffentlichkeitsarbeit; Informationsverbreitung; Gesamtwirtschaftliche Produktion